THE RULE OF THE BALANCED SCORECARD TO ACHIEVE THE COMPETITIVE ADVANTAGE APPLIED RESEARCH ON THE FARUK STATE ENTERPRISE FOR CONSTRUCTION CONTRACTS - Noor Fadhil Shahatha; Mohammed T Mohammed (Scholar Express Journals, 2022)
Competition is a very difficult process in an open work environment, so the companies have to find a competitive advantage to make it survive inside the work environment. Implementing conventional management tools would lead the organization to lose its competitive advantages because the conventional management tools can’t determine the strength and weaknesses of the organization, so it started to implement new tools that manage the costs, one of these tools is the balanced scorecard. Implementing it would help the organization to achieve a competitive advantage, through the analyzing of the elements of the balancing scorecard, and implementing them annually to know the strength and weakness of the organization, and to determine the improvement and the weakness that has hit the organization through. the lower ratios in the practical aspects we recommend to the companies to use the balanced scorecard to be aware of the low ratios and the negative sides to avoid them to achieve a competitive advantage.
Keywords: Balanced scorecard; competitive advantage; evaluate performance